Development of Smart Ethno-STEM (System of Mobile Augmented Reality Technology) in Organic Chemistry to Enhance Students’ Metacognitive Skills and Scientific Literacy - Yogo Dwi Prasetyo; Ayu Tri Khodizah; Novan Alkaf Bahraini Saputra (Postgraduate, University of Mataram, 2025)
Learning in Stereochemistry still tends to lack contextualization and the integration of technology and ethnosciences. This study aims to develop and evaluate Smart Ethno-STEM (System of Mobile Augmented Reality Technology) as an innovative learning medium in organic chemistry, particularly on stereochemistry topics, to enhance students’ metacognitive skills and scientific literacy. The research employed a Research and Development (R&D) design using the ADDIE model, involving validation, practicality, and effectiveness testing. The data were analyzed using descriptive validation and practicality scores, N-Gain, and MANOVA analysis. Validation results from one media expert and two material experts indicated that the media was categorized as highly valid (average score 4.46). Practicality tests conducted with 16 students showed a very practical use (average score of 4.75). The effectiveness test showed significant improvements in both metacognitive skills and scientific literacy, with N-Gain scores in the high category in the experimental group (metacognition 0.75; literacy 0.72) and in the medium category in the control group (metacognition 0.59; literacy 0.57). MANOVA results confirmed a significant influence of the class factor on both variables simultaneously (Sig. Hotelling’s Trace = 0.013). These findings demonstrate that Smart Ethno-STEM effectively enhances students’ higher-order thinking skills and connects scientific concepts with socio-cultural contexts, offering a contextual and technology-based solution for organic chemistry learning